The meaning of selected questionnaires in assessment of quality of life in patients with gastroesophageal reflux disease - Bąk, Elzbieta; Wojtuń, Stanisław; Gil, Jerzy; Dyrla, Przemysław (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Questionnaires are valuable tools for assessing the quality of life,in patients with chronic gastroesophageal reflux disease. They help to plan adequate care of patients with chronic disease,ensuring an optimum level of vital activity for them. Gastroesophageal Reflux disease can disable biopsychosocial functioning.of patients,making their daily functioning difficult. Database ‘PubMed’ was searched using the following key words: quality of life, gastroesophageal reflux disease and questionnaires for assessment quality of life. The aim of this study is to provide characteristics of general questionnaires, used to assess quality of life in patients with GERD. The paper aids understanding of the questionnaires’ role and their appropriate use. A carefully selected questionnaire may help achieve a holistic view of the patients with chronic gastroesophageal reflux disease. It will help better understand the impact of disease on patients’ daily functioning and, (if required) make modifications to a given treatment plan according to patients’ needs.